Strengthening Teacher Performance through Professional Ethics: Evidence from Islamic Religious Education Teachers in Indonesia - Sutriana Sutriana; Rosmiati Ramli; Sumadin Sumadin; Dadang Sumarna; Raya Mangsi (CV. Gerasi Insan Nusantara, 2026)
Professional ethics has become an increasingly important issue in educational improvement, particularly in the context of Islamic Religious Education (IRE), where teachers are expected to serve not only as instructors but also as moral role models. Despite extensive discussions on teacher professionalism, limited research has explored how professional ethics contributes to teacher performance within Islamic educational settings. This study investigates the implementation of professional ethics among Islamic Religious Education teachers and its contribution to teacher performance at SMP Negeri 1 Baraka, Enrekang Regency, Indonesia. Employing a qualitative case study design, data were collected through in-depth interviews, participant observations, and document analysis involving certified IRE teachers, school leaders, and relevant educational stakeholders. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, while trustworthiness was ensured through triangulation, prolonged engagement, and member checking. The findings reveal that professional ethics are consistently implemented across personal, social, pedagogical, and professional dimensions. Teachers demonstrate strong moral integrity, professional responsibility, collaborative behavior, and commitment to continuous professional development through participation in teacher professional forums. Furthermore, ethical practices significantly influence instructional planning, classroom management, assessment implementation, and overall teaching effectiveness. The study concludes that professional ethics function not only as a moral framework but also as a strategic mechanism for enhancing teacher performance and educational quality. These findings provide practical implications for teacher development programs and contribute to the broader discourse on ethics-based educational professionalism in Islamic education.